2020
DOI: 10.3897/neobiota.62.52723
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Environmental Impact Classification for Alien Taxa (EICAT): a summary of revisions to the framework and guidelines

Abstract: The Environmental Impact Classification for Alien Taxa (EICAT) classifies the impacts caused by alien species in their introduced range in standardised terms across taxa and recipient environments. Impacts are classified into one of five levels of severity, from Minimal Concern to Massive, via one of 12 impact mechanisms. Here, we explain revisions based on an IUCN-wide consultation process to the previously-published EICAT framework and guidelines, to clarify why these changes were necessary. These changes ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 28 publications
1
34
0
Order By: Relevance
“…reviews) but always search for primary reports (but see Sheet S1, for inaccessible primary reports). In accordance with the EICAT standards (IUCN, 2020a; Volery et al, 2020), only observed impacts were classified; potential, hypothetical, projected or extrapolated impacts were considered non‐relevant (but see Sheet S2, for non‐relevant information sources). Species for which no impact observation was found were classified as Data Deficient (IUCN, 2020a).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…reviews) but always search for primary reports (but see Sheet S1, for inaccessible primary reports). In accordance with the EICAT standards (IUCN, 2020a; Volery et al, 2020), only observed impacts were classified; potential, hypothetical, projected or extrapolated impacts were considered non‐relevant (but see Sheet S2, for non‐relevant information sources). Species for which no impact observation was found were classified as Data Deficient (IUCN, 2020a).…”
Section: Methodsmentioning
confidence: 99%
“…alien taxon directly interacts with the impacted native taxon) and indirect (i.e. alien taxon modifies another factor of the environment, thereby indirectly affecting the native taxon) mechanisms (Volery et al, 2020). Uncertainty was captured by assigning a confidence level (high, medium or low) to each observation indicating how confident the assessor is that the assigned magnitude is the ‘true’ one (IUCN, 2020b; Volery et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although a level of subjectivity is inevitable, some of this uncertainty may be reduced through improvement in the protocol, such as the refinement of guidelines, which is already reflected in the succession of EICAT guidelines (Blackburn et al 2014;Hawkins et al 2015;IUCN 2020a). However, clarification about the changes and ensuring these are effectively communicated will be important to maximise consistency (see Volery et al 2020, as the application of different versions of the guidelines may further lead to inconsistencies across different assessments. Conducting workshops, training sessions and developing online tools that help guide assessors through the process-giving examples where uncertainty is most likely to arise-might help reduce these uncertainties.…”
Section: Biases In the Data Assessmentmentioning
confidence: 99%
“…ICAT Schemes are two evidence-based classification systems for evaluating the ecological and socioeconomic impacts of non-native species (Blackburn et al 2014;Bacher et al 2017). Their assessment requires the collection and evaluation of all the papers reporting data on impacts produced by the target species in its global introduction range and their scoring according to different mechanisms of impact (Volery et al, 2020). Due to the high number of species to assess, we used an expert-based approach where single experts used ICAT Schemes as reference systems for scoring the species after a rapid search of literature and without considering the mechanism of impact.…”
Section: Discussionmentioning
confidence: 99%